Quantifying structural modifications of gills of two fish species Astyanax altiparanae (Lambari) and Prochilodus lineatus (Curimbata) after exposure to biodegradable detergents in urban lake water - Pereira, Bruno Fiorelini; Alves, Anderson Luis; Senhorini, Jose Augusto; Scalize, Priscilla Hakime; Tocchini De Figueiredo, Fellipe Augusto; Pitol, Dimitrius Leonardo; Caetano, Flavio Henrique [UNESP] (Taylor & Francis Inc, 2017)
Anthropic actions in rivers and urban lakes are a cause for concern to our ecosystem. The effects on fauna and flora of substances discharged into waterways have become a focus for investigations globally. Biodegradable detergents are widely used in residences and small industries, but little is known regarding the consequences on fish fauna. The objective of the present study was to identify modifications in gill structure in two fish species, Astyanax altiparanae and Prochilodus lineatus, after treatment with water obtained from an urban lake and an exposure to 1 ppm diluted biodegradable detergents (linear alkylbenzene sulfonate). Data demonstrated exposure to urban lake produced various alterations in gill functions such as lamellar fusions, aneurysms, mucous, and chlorine cell proliferation, which may be attributed to the presence of detergents in the water but may also be a consequence of synergetic actions of detergents with other pollutants. Results showed that the levels of NO2-, Na, F-, Cl-, and Fe were significantly higher in urban lake water but in the presence of detergents Ni was also detected. Evidence indicates that biodegradable detergents produce damage to gill functions, which subsequently alters the fish physiology and reduces the ability to cope with stress and survival.